1975
DOI: 10.1007/bf01971376
|View full text |Cite
|
Sign up to set email alerts
|

Differences of reabsorption of unconjugated BSP and BSP-glutathione from the rat biliary tree after retrograde intrabiliary injection

Abstract: It has been shown that water and electrolytes are reabsorbed from the biliary tract of the rat. Furthermore there are some suggestions for the reabsorption of organic compounds during their passage down the biliary tract. Our results presented in this paper demonstrate a different mode of biliary excretion of unconjugated BSP [BSP-U] and BSP- glutathione [BSP-GSH] after retrograde intrabiliary injection, BSP-GSH is excreted to a much greater extent than BSP-U within the first 5 minutes after retrograde adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Since such inhibitor may also inhibit P‐gp, the mdr1a/b (−/−) mice were used to avoid effect of P‐gp on the intestinal absorption. BSP is a quite potent inhibitor of various OATP family members with an inhibition constant of 0.3–20 µM,29 whereas BSP would stably exist inside the intestinal lumen due to its low gastrointestinal absorption demonstrated in rats 30. Coadministration of BSP at 30 mg/kg body wt decreased plasma concentration of celiprolol after oral absorption in mdr1a/b (−/−) mice (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Since such inhibitor may also inhibit P‐gp, the mdr1a/b (−/−) mice were used to avoid effect of P‐gp on the intestinal absorption. BSP is a quite potent inhibitor of various OATP family members with an inhibition constant of 0.3–20 µM,29 whereas BSP would stably exist inside the intestinal lumen due to its low gastrointestinal absorption demonstrated in rats 30. Coadministration of BSP at 30 mg/kg body wt decreased plasma concentration of celiprolol after oral absorption in mdr1a/b (−/−) mice (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…This has not been proven yet. The RPB -technique most probably under-estimates biliary tree volume since it has been shown that by RII, BSP as well as india ink are not distributed homogenously in the biliary system of the rat (5,6). Both dyes showed a patchy distribution in the biliary tree and vast parts of the biliary system were not reached after RII.…”
Section: Discussionmentioning
confidence: 95%
“…(2). Water, electrolytes and glutathione deriving products are partially reabsorbed in the biliary lumen after secretion; the reabsorption process depends on the concentration of solutes and on their contact time with the biliary tree [27]. Such reabsorptive process can be seen as a cholehepatic shunt resulting in continous intrahepatic recycling of these bile constituents [28].…”
Section: Biliary Glutathione Secretion and Bile Formationmentioning
confidence: 99%